2018
DOI: 10.1016/j.jep.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided isolation and UHPLC-DAD-ESI-MS/MS quantification of potential anti-inflammatory phenolic compounds from flowers of Inula montana L

Abstract: Flowers extracts and isolated compounds present promising anti-inflammatory activity which provides a scientific basis for the traditional use of Inula montana and may be proposed in the same indications as Arnica montana. The developed and validated simple, accurate and rapid UHPLC method can be used for the quality control of the herbal drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
6
12
0
Order By: Relevance
“…Bioassay-guided fractionation is a well-established approach for untargeted, but focused screening of active compounds in complex matrices. [44][45][46][47][48] From the identified compounds (Table S2 †), p-cymene, cinnamyl alcohol, cinnamic acid and cinnamalde-hyde are present in Cinnamomum verum extract, with the latter as major active principle. 15,24,49,50 To the best of our knowledge, the other compounds shown in Table S2 † were not reported to be present in cinnamon extract so far.…”
Section: Discussionmentioning
confidence: 99%
“…Bioassay-guided fractionation is a well-established approach for untargeted, but focused screening of active compounds in complex matrices. [44][45][46][47][48] From the identified compounds (Table S2 †), p-cymene, cinnamyl alcohol, cinnamic acid and cinnamalde-hyde are present in Cinnamomum verum extract, with the latter as major active principle. 15,24,49,50 To the best of our knowledge, the other compounds shown in Table S2 † were not reported to be present in cinnamon extract so far.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds from Inula montana L. possessed promising anti-inflammatory activity through inhibition of NO production in murine macrophages RAW 264.7 cell line, jaceoside ( 14 ) (Figure 2) being the compound most active with IC 50 of 0.34 ± 0.01 μM, being several times better than the positive control drug dexamethasone (IC 50 of 3.89 ± 0.94 μM) [63].…”
Section: Secondary Metabolites From Inula Species Against Oxidativmentioning
confidence: 99%
“…It has been also reported that different extracts from I. helenium roots contained 5‐CQA (35.5–47 mg/100 g DW) and dicaffeoylquinic acid (60.8–73.4 mg/100 g DW) . The flowers of I. montana contained between 0.39–0.41 % of mono‐ and 0.92–14.41 % of dicaffeoylquinic acids . 1,5‐DCQA was the main component of I. crithmoides roots (0.035 % w/w) .…”
Section: Resultsmentioning
confidence: 91%
“…Plants belonging to this genus have shown to possess various biological activities–anti‐inflammatory, antitumor, antibacterial, antitussive, antiproliferative, antioxidant, antidiabetic and hepatoprotective, etc., which were attributed to the abundance of bioactive components mainly sesquiterpene lactones, phenolic acids, and flavonoids . Chlorogenic acid and dicaffeoyl esters of quinic acid have been also reported in some Inula species …”
Section: Introductionmentioning
confidence: 99%